TREATMENT OF ADHESIVE CAPSULITIS WITH THE TRIPLE PROCEDURE: INTRA-ARTICULAR INJECTION WITH CORTICOSTEROIDS, HYDRODILATION AND SHOULDER MANIPULATION UNDER SEDATION - Mauro Emilio Conforto Gracitelli; Jorge Henrique Assunção; Micael de Mesquita Paiva; Fernando Brandão de Andrade e Silva; Arnaldo Amado Ferreira Neto; Eduardo Angeli Malavolta (Acta Ortopédica Brasileira)
ABSTRACT Objective: There are several conservative treatment options for adhesive capsulitis (AC), but no previous study combines hydrodilation, corticosteroid injection and joint manipulation under sedation (triple procedure), followed by daily home exercises. Methods: Patients included were evaluated before the procedure, at 30 days, 3, 6 and 12 months after treatment in prospective cohort. The outcomes used were the ASES, UCLA, SANE, VAS scales and passive range of motion (ROM). Results: 65 shoulders of 63 patients were included. The mean ASES score progressed from 37.7 ± 17.9 to 94.1 ± 10.3 at 12 months after the procedure (p < 0.001). The mean UCLA went from 15.9 ± 5 to 33.2 ± 2.8 and SANE from 50.4 ± 18.3 to 94.3±9.0. At 12 months, the passive elevation improved from 114°±24° to 176° ± 6°, external rotation in neutral from 29° ± 17° to 72° ± 11° and internal rotation in neutral from 18.6 ± 3.6 points to 9.4 ± 2.4 points. No patient presented a fracture after manipulation. Conclusions: Treatment with the triple procedure resulted in a statistically and clinically relevant improvement in functional results and gains in shoulder range of motion, with no reports of complications. Level of evidence IV, Prospective study.